The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1515/applirev-2022-0049
|View full text |Cite
|
Sign up to set email alerts
|

Success factors for English as a second language university students’ attainment in academic English language proficiency: exploring the roles of secondary school medium-of-instruction, motivation and language learning strategies

Abstract: Displaying a strong competence in English as a second language (L2) is a major advantage for university graduates in personal development and career advancement. There are limited studies that have explored how the implementation of English-Medium-Instruction (EMI) in non-Anglophone universities can affect students’ academic English proficiency. This mixed-method study explores how both the learners’ variables (motivation and L2 learning strategies) and the medium-of-instruction policy implemented at secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…The findings indicate that metacognitive and cognitive strategies were ranked as being the highest used strategies linked to proficiency. This finding agrees with Tai & Zhao's (2022) results indicating that the use of cognitive and metacognitive strategies predicted higher success in English learning among university students in Hong Kong. Conversely, studies on other cultures named other types as being the most used, such as social strategies in China (Ma & Abdul Samat, 2022), compensation strategies in Thailand (Zou & Arab World English Journal www.awej.org ISSN: 2229-9327 42 Supinda, 2022), and affective strategies in Turkey (Tezcan & Deneme, 2016).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The findings indicate that metacognitive and cognitive strategies were ranked as being the highest used strategies linked to proficiency. This finding agrees with Tai & Zhao's (2022) results indicating that the use of cognitive and metacognitive strategies predicted higher success in English learning among university students in Hong Kong. Conversely, studies on other cultures named other types as being the most used, such as social strategies in China (Ma & Abdul Samat, 2022), compensation strategies in Thailand (Zou & Arab World English Journal www.awej.org ISSN: 2229-9327 42 Supinda, 2022), and affective strategies in Turkey (Tezcan & Deneme, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Contrary to many previous studies, this study found no effect of gender or school background on strategy use or the results of the CQS. The decreasing effect of school background on the development of English language proficiency at the university level was similar to the findings of Tai and Zhao (2022) on students in Hong Kong. It is also very promising given the fact that the Saudi government schools were under improvement in the past two decades to catch up with private and international schools and earlier studies such as Aburizaizahet al ( 2016) noted that graduates at that time did not reflect that because the improvements haven't been fully implemented.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations